Undiagnosed bleeding disorder and pediatric airway: Prudence of ananesthetist prevails! (Indian Journal of Case Reports, 2026)
A 7-year-old, 28-kg male child with cerebral palsy and intellectual disability was diagnosed to have left-sided pelvi-ureteric junction obstruction and left hydronephrosis, for which he was planned for left-sided pyeloplasty under general anesthesia. The patient had developed a spontaneous oro-nasal bleed, which was managed successfully in the perioperative period without any hemodynamic instability and perioperative respiratory adverse events (PRAE). The patient was extubated on the table without any airway complications after confirming complete neuromuscular blockade recovery